MRNA profiling: Application to an old casework. (December 2017) - Fabbri, M.; Venturi, M.; Talarico, A.; Inglese, R.; Gaudio, R.M.; Neri, M.
Abstract: Present work showed the application of mRNA profiling to an old casework where routinely methods used for specific blood identification revealed negative results. Analysis involved a sweater worn by the suspect as claimed by two witnesses. No blood stains were found during routine examination. When luminol was applied, three areas of luminescence developed. In order to confirm the presence of human blood, traces were collected using sterile cotton-tipped swabs and tested using HemDirect Hemoglobin test (SERATEC ® ). All specimens tested were negative. Relating to the novel and sensitive mRNA blood-specific markers profiling, material previously collected was sampled again and tested on three blood specific markers HBB, ALAS2 and CD93, together with two housekeeping genes represented by ACTB and 18S-rRNA. All samples were positive for all three blood specific mRNA markers.